Lost Horizons: The Unseen Consequences of Urbanization on Bengaluru’s Lakes - Shivram Jetgond (Calibrating Urban Livability in the Global South, 2024)
Once known for its many lakes, Bengaluru’s rapid urbanization has led to puzzling phenomena such as the loss and disappearance of aquatic life. This case study explores the alarming disappearance of lakes from the city, which is largely linked to rampant urban growth and inadequate environmental protection. In the past, Bengaluru was known for its vast network of lakes, which were essential for maintaining the natural balance. and to provide water for local residents and wildlife. But relentless urbanization, lakebed encroachment, pollution and uncontrolled development are slowly but surely leading to the loss of these vital waterways. The impact of this loss is far-reaching, exacerbating the region’s water scarcity problems while affecting the local ecosystem. The city’s water supply may not be sustainable in the long term, as shrinking lakes contribute to reduce the groundwater recharge, which affects the total amount of groundwater. A comprehensive strategy involving urban planning, government action and community engagement is needed. solve this problem. The case study explores revitalization options, community-led projects and strict land use laws as tools to preserve and enhance Bengaluru’s lakes. Immediate action is needed to halt this trend and ensure the conservation of these vital natural resources for the benefit of the city’s residents and the environment.